The Activation of Endothelial Cells Relies on a Ferroptosis-Like Mechanism: Novel Perspectives in Management of Angiogenesis and Cancer Therapy - Lopes-Coelho, Filipa; Martins, Filipa; Hipólito, Ana; Mendes, Cindy; Sequeira, Catarina O.; Pires, Rita F.; Almeida, António M.; Bonifácio, Vasco D. B.; Pereira, Sofia A.; Serpa, Jacinta (Frontiers in Oncology, 2021)
The activation of endothelial cells (ECs) is a crucial step on the road map of tumor angiogenesis and expanding evidence indicates that a pro-oxidant tumor microenvironment, conditioned by cancer metabolic rewiring, is a relevant controller of this process. Herein, we investigated the contribution of oxidative stress-induced ferroptosis to ECs activation. Moreover, we also addressed the anti-angiogenic effect of Propranolol. We observed that a ferroptosis-like mechanism, induced by xCT inhibition with Erastin, at a non-lethal level, promoted features of ECs activation, such as proliferation, migration and vessel-like structures formation, concomitantly with the depletion of reduced glutathione (GSH) and increased levels of oxidative stress and lipid peroxides. Additionally, this ferroptosis-like mechanism promoted vascular endothelial cadherin (VE-cadherin) junctional gaps and potentiated cancer cell adhesion to ECs and transendothelial migration. Propranolol was able to revert Erastin-dependent activation of ECs and increased levels of hydrogen sulfide (H2S) underlie the mechanism of action of Propranolol. Furthermore, we tested a dual-effect therapy by promoting ECs stability with Propranolol and boosting oxidative stress to induce cancer cell death with a nanoformulation comprising selenium-containing chrysin (SeChry) encapsulated in a fourth generation polyurea dendrimer (SeChry@PUREG4). Our data showed that novel developments in cancer treatment may rely on multi-targeting strategies focusing on nanoformulations for a safer induction of cancer cell death, taking advantage of tumor vasculature stabilization.